Sodium hydrosulfide alleviates mitochondrial injury of rat myocardial cell line H9C2 induced by high glucose and high fat - ZHANG Weicai, LIU Siren, WANG Shangnong (Jichu yixue yu linchuang, 2023)
Objective To investigate the function of sodium hydrosulfide (NaHS) to regulate mitochondrial fusion/fission in diabetic cardiomyopathy and underlying mechanism. Methods Db/db mice as type 2 diabetes animal model were treated by NaHS. H9C2 cells incubated with glucose (40 mmol/L), palmitic acid (200 μmol/L, Pal) and oleate (200 μmol/L, Ole) were intervened by NaHS (100 μmol/L). H2C9 cells were divided into control, HG+Pal+Ole, HG+Pal+Ole+NaHS and Pal+Ole+DJ-1 siRNA+NaHS groups. The protein level of Mfn2, Fis1, CSE, and DJ-1 was determined by Western blot. Mitotracker staining was used to observe the morphology of mitochondria. The ultra-structural alteration of cardiac tissues was detected by transmission electron microscopy. The cardiac functions were detected by echocardiography. Results Expression of Fis1 was increased (P＜0.05) and expression of Mfn2 was decreased (P＜0.05) in db/db and H9C2 treated by HG+Pal+Ole compared to control group. NaHS could upregulate the expression DJ-1, enhance the expression of Mfn2, and reduce the expression of Fis1. In db/db mice, cardiac systolic function was reduced. Disordered arrangement of myofilament, loss of cristae and mitochondrial fission were observed. NaHS could ameliorate these alterations. Conclusions NaHS may alleviate mitochondria injury by promoting mitochondrial fusion.